2002
DOI: 10.1038/sj.cgt.7700519
|View full text |Cite
|
Sign up to set email alerts
|

The combination of HSV-tk and endostatin gene therapy eradicates orthotopic human renal cell carcinomas in nude mice

Abstract: Background and methods: Gene therapy may offer a new tool for the treatment of renal cell carcinoma ( RCC ). We have tested a combination of cytotoxic and antiangiogenic gene therapy for wild -type orthotopic human RCC xenografts in nude mice using intratumoral adenovirus -mediated herpes simplex virus thymidine kinase ( HSV -tk ) and endostatin ( ES ) gene therapy. In vivo magnetic resonance imaging, morphometry, immunocytochemistry, and survival were used to evaluate the treatment effect. Adenovirus -mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
(34 reference statements)
2
14
0
Order By: Relevance
“…Experimental combination therapy with endostatin has exhibited some successful synergistic effects on primary tumor growth, [42][43][44] correlating with the results of our study. However, the present experimental models did not focus on any antimetastatic effects that might have been evident.…”
Section: Discussionsupporting
confidence: 82%
“…Experimental combination therapy with endostatin has exhibited some successful synergistic effects on primary tumor growth, [42][43][44] correlating with the results of our study. However, the present experimental models did not focus on any antimetastatic effects that might have been evident.…”
Section: Discussionsupporting
confidence: 82%
“…Gene therapy has become a promising strategy for the treatment of gastric cancer [27][28][29][30][31] , in which the transfer of suicide genes into tumor cells has emerged as an attractive modality for the selective elimination of cancer cells [14][15][16]30,31] . The suicide genes encode non-mammalian enzymes that can convert nontoxic prodrugs into cellular toxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…One of the landmark discoveries for this therapeutic strategy is the transfer of suicide genes, such as HSV-TK, into the tumor cells, which has been shown to exert antitumor efficacy on a variety of cancer cells [8][9][10][11] . The expressed HSV-TK/ganciclovir (GCV) system can not only inhibit the DNA synthesis of the target cells but also produce a bystander effect against tumors [12][13][14][15][16] . However, these effects have been found to be unstable in some of the transfected cells, which may result in a decreased efficiency in the treatment of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide gene therapy with the herpes simplex virus thymidine kinase (HSV-TK) fragment, the most widely used strategy for the cancer therapeutic study [3] , has been shown to exert antitumor efficacy in various cancer models [4][5][6][7] . However, its efficacy seems not to be fully developed to eliminate tumor cells in some of the investigations [8][9][10][11][12] . Gene therapy with HSV-TK and cytokine genes together may produce a complementary effect, and has become a new insight for the treatment of malignancies [13,14] .…”
Section: Introductionmentioning
confidence: 99%